Temporal Preparation Driven by Rhythms is Resistant to Working Memory Interference - de la Rosa, María D.; Sanabria, Daniel; Capizzi, Mariagrazia; Correa, Ángel (Frontiers in Psychology, 2012)
It has been recently shown that temporal orienting demands controlled attention (Capizzi, Sanabria, & Correa, 2012). However, there is current debate on whether temporal preparation guided by regular rhythms also requires the generation of endogenous temporal expectancies or rather involves a mechanism independent of executive control processes. We investigated this issue by using a dual-task paradigm in two different experiments. In Experiment 1, the single-task condition measured reaction time to respond to the onset of an auditory stimulus preceded by either a regular or an irregular auditory rhythm. The dual-task condition additionally included a working memory task, which demanded mental counting and updating. In Experiment 2, the simultaneously WM task was a variant of the Sternberg Task. We hypothesized that, if temporal preparation induced by rhythms did not involve executive processing, it would not be interfered by the simultaneous working memory task. The results showed that participants could anticipate the moment of target onset on the basis of the regular rhythm and, more important, this ability resisted the interference from the double task condition in both experiments. This finding supports that temporal preparation induced by rhythms, in contrast to temporal orienting, does not require resources of executive control.